Crystal structure of hexacarbonyl bis(μ2-2-methoxybenzenethiolato-κ2S)pyridine(triphenylphosphane)dirhenium(I), C43H34NO8PS2Re2 - Nkoe Pheello Isaac; Koen Renier; Brink Alice; Schutte-Smith Marietjie (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C43H34NO8PS2Re2, monoclinic, P21/c (no. 14), a = 12.165(8) Å, b = 19.027(11) Å, c = 18.848(14) Å, β = 108.735(2)°, V = 4131(5) Å3, Z = 4, Rgt(F) = 0.0308, wRref(F2) = 0.0683, T = 100(2) K.